Interview of Howard O. Wessbecher by Brian Shoemaker - Wessbecher, Howard O. (Byrd Polar Research Center Archival Program, 2008)
Baker, Dave, p. 60 Bergstrum, Jim, pp. 59-60 Bowers, Dick, pp. 51-53, 58-59 Condit, Father (priest), p. 70 Dufek, Admiral George, pp. 53, 55-56, 69, 72-73 Glendyer, Jay, pp. 3, 42-43 Goodale, Edward L., pp. 3, 42-43, 62 Haglan, Mel, pp. 7-8 Harrison, Richard, p. 6 Jones, Elmo, pp. 57-58 Molton, Ken, pp. 3, 42-46 Nash, Jack, p. 49 Siple, Paul, pp. 50, 72 Wilkins, Sir Hubert, pp. 43-44 Woods, Ernest, p. 43 The media can be accessed at the links below. Audio Part 1: http://streaming.osu.edu/knowledgebank/byrd/oral_history/Mr_Howard_Wessbecher_1.mp3 Audio Part 2: http://streaming.osu.edu/knowledgebank/byrd/oral_history/Mr_Howard_Wessbecher_2.mp3 Howard Wessbecher served at the Alert and Resolute sites in the Arctic region, as well as McMurdo in Antarctica. He wintered over in all three places. Earlier in his career, he served in WWII, completed a degree in forestry, and accepted a position with the Weather Bureau. His first major assignment (April 1952 until March 1953) was as storekeeper in Resolute Bay, in remote northern Canada. The small base had only 12 persons, six Americans and six Canadians. Four smaller satellite stations, with eight people each, were in outlaying regions. Resolute was re-supplied twice a year by the Air Force, once in the spring and once in the fall. Wessbecher adjusted well to the isolation and harsh conditions. At Resolute, and the other stations as well, there was a radiosonde program that involved launching weather balloons twice a day into the upper atmosphere. The radiosonde was a small box with a radio transmitter, and a pressure gauge. Using radio signals it gave readings for humidity, temperature, air pressure, wind speed and direction. At first the men made their own hydrogen gas for launching the balloons. Later the Weather Bureau supplied much safer helium gas. There was also a glaciological study program at Resolute which involved measuring the thickness of sea ice, and analyzing the depth, gradations, and composition of snow layers. Once a day, Wessbecher ventured out ...